UV Photodetector Based On P-N Junction Of Nickel Oxide Thin Films And N-Type Silicon Prepared By Thermal Oxidation - Nomaan, Ahlaam T.; Al-Hardan, Naif H.; Ahmed, Naser M.; Ng, Sha Shiong; Aziz, Azlan Abdul (2019)
Transition metal oxides semiconductors are well known multifunction compounds, some show an n-type behaviour such as zinc oxide, titanium oxide and the others behave as p-type semiconductors. In this study nickel oxide (NiO) thin films (as a p-type semiconductor) was prepared via two-step process, first Ni metal is thermally evaporated on an n-type silicon substrate in high vacuum thermal evaporation unit, then thermal oxidation was employed to convert the Ni metal to NiO in a controllable tube furnace at atmospheric ambient. The prepared thin films were characterized through X-ray diffraction to verify its phase structures, ultraviolet–visible spectrophotometry to study its optical properties. The prepared p-n junction based on NiO thin films and the Si substrate was tested as UV-visible photodetector. The results show a blind sun light photodetector with high selectivity to UV light. The device performance as a UV photodetector will be explored.